A Study on the Relationship of Consumers’ Mental Image and Perceived Values of Brand Products - Behnoush Jovari (International Journal of Management, Accounting and Economics, 2018)
Today’s competitive world has transformed the role of consumers in organizations, as consumers are present in all processes, from production phases to the delivery of products. Thus, the universities researchers’ and traders’ attention have shifted towards the consumers’ mental image of the brands to the extent that they have included allocated sections in their mission statements and company objectives to the consumers’ mental image. The present article attempts to study the effect of the Shampoo Brand’s mental image on the perceptual values of the consumers. In this perspective, the present research is applied and is descriptive. The purchase process and preserving the health of hair, scalp and reducing hair loss and the most important of all, maintaining the beauty of appearance is of outmost importance for women; choosing the right shampoo is always their crucial concerns specifically in Islamic societies like Iran where the hair is covered throughout the day and the absence of breathing scalp gets highlighted. Thus, participants include the Alzahra female students shampoo consumers who has responded to the questionnaire as the main research tool. The analysis using SPSS and LISREL proved research hypothesis. That is, the mental image of brand is positively related to perceived quality and price/cost of the products. Considering that perceived quality and price the elements of perceived value, results confirm such relationship in Alzahra University as the only Iranian women university.